An innovation bootcamp model to develop HIV self-testing social enterprise among young people in Nigeria: a youth participatory design approach. Issue 1 (April 2020) - Nwaozuru, Ucheoma; Gbajabiamila, Titilola; Obiezu-Umeh, Chisom; Uzoaru, Florida; Mason, Stacey; Tahlil, Kadija; Oladele, David; Musa, Adesola; Idigbe, Ifeoma; Airhihenbuwa, Collins; Ezechi, Oliver; Tucker, Joseph; et al.
Abstract: Background: There is a critical gap in the uptake of HIV testing among young people in sub-Saharan Africa. In Nigeria, only a quarter of young people aged 14–24 years have ever tested for HIV. Recent evidence suggests that HIV self-testing (HIVST) may play a role in addressing gaps in HIV testing coverage and serve as an entry point for HIV prevention services. However, there is limited information on strategies that may increase the uptake of HIV testing among young people. Current strategies rarely include young people in the design stages, which often results to poor adoption of HIV interventions. We aimed to address this gap with the development of an innovation bootcamp for participants aged 14–24 years to generate interventions to promote HIVST among young people in Nigeria. Methods: The innovation bootcamp was a 4-week accelerated training programme to build entrepreneurial and research capacities among young people to develop HIV self-testing social enterprise. The training programme consisted of social enterprise and research development modules. At the completion of the bootcamp, we also examined participants' perspectives of the programme using surveys. Findings: Between May 6 and May 30, 2019, 20 people participated in the innovation bootcamp in Lagos State, Nigeria; 13 (65%) were male and age range was 22–24 years. The innovation bootcamp generated five youth-participatory HIVST social enterprises. Two of the social enterprise focused on repacking HIVST kits to increase their appeal among young people, one idea focused on leveraging community engagement platforms (vocational skills training and youth community events) to promote HIVST, and another social enterprise seeks to use a reward-referral system to promote HIVST in young people. Participants' survey responses suggest that the innovation bootcamp fostered an environment for young people to connect with their peers to generate ideas and solutions. The bootcamp also provided opportunities for skills development such as logistics management and research (protocol writing, data collection, and needs assessment) skills. Interpretation: The innovation bootcamp model can leverage the resourcefulness, capabilities, and resilience of youth to generate youth-centred and youth-sensitive interventions to promote HIV testing. The innovation bootcamp led to the development of five youth-centred and participatory interventions to promote uptake of HIV self-testing among young people in Nigeria. Funding: Eunice Kennedy Shriver National Institute of Child Health and Human Development Grant number: 1UG3HD096929 and NIAID K24AI143471